Dentinal Crack Formation and Quality of Obturation Using Two Single File Systems and Two Obturation Techniques: A micro-CT Study. - Shaban Shaban Omar; Bahar Jafaar Selivany (Erbil Dental Journal)
Background and objectives: Root canal preparation following obturation with rotary instruments and different obturation techniques may lead to formation of microcracks in the root canal wall, void and gaps between the canal wall and obturation material.